Prevalence of Intimate Partner Violence and Associated Factors Among Men Who Have Sex with Men in China - Wei, Dannuo (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) in the heterosexual population has gained increasing public concern in China, but little is known about it among men who have sex with men (MSM).1 This study aimed to investigate the prevalence of IPV and associated factors among MSM in Chengdu, China. Participants were recruited from a local MSM-friendly health consulting center. This study used the adjusted Intimate Partner Violence Scale among Gay and Bisexual Men (IPV-GBM scale) to capture lifetime IPV experiences including physical, sexual and emotional violence, monitoring, and controlling behaviors. Among 431 participants, 153 (35.5%) reported any IPV experiences, and 119 (27.6%) reported themselves as being the perpetrator. Adjusted logistic regression models revealed that having been engaged in transactional sex was positively associated with victimization through monitoring behaviors (adjusted odds ratio [ORa] = 2.7, 95% confidence interval CI = [1.7, 7.4]) and perpetration of monitoring behaviors (ORa = 3.9, 95% CI = [1.5, 13.3]); drug use was positively associated with victimization through controlling behaviors (unadjusted odds ratio [ORu] = 2.5, 95% CI = [1.2, 5.0]) and emotional violence (ORa = 1.9, 95% CI = [1.0, 3.5]); older age (≥18 years) of first homosexual intercourse was negatively associated with perpetration of physical violence (ORu = 0.3, 95% CI = [0.2, 0.7]) and sexual violence (ORu = 0.4, 95% CI = [0.2, 1.0]); higher self-esteem was negatively associated with both victimization and perpetration of sexual and emotional violence. We found that victimization and perpetration experiences were correlated in all dimensions of IPV. Violence was prevalent among MSM and merits public attention. This study provides more evidence about IPV among Chinese MSM and identifies two significant factors contributing to IPV (self-esteem and age of first homosexual intercourse), which have been overlooked in previous studies. Researchers should take these factors into consideration for interventions developments.